2018
DOI: 10.1111/1755-0998.12783
|View full text |Cite
|
Sign up to set email alerts
|

HiMAP: Robust phylogenomics from highly multiplexed amplicon sequencing

Abstract: High-throughput sequencing has fundamentally changed how molecular phylogenetic data sets are assembled, and phylogenomic data sets commonly contain 50- to 100-fold more loci than those generated using traditional Sanger sequencing-based approaches. Here, we demonstrate a new approach for building phylogenomic data sets using single-tube, highly multiplexed amplicon sequencing, which we name HiMAP (highly multiplexed amplicon-based phylogenomics) and present bioinformatic pipelines for locus selection based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 117 publications
(162 reference statements)
2
24
2
2
Order By: Relevance
“…Also, Kunprom et al (Kunprom et al 2015) reported a strongly divergent COI lineage within B. correcta, matching earlier results based on the COI-3P region (Jamnongluk et al 2003). They attributed this anomaly to Wolbachia bacterial infection, but upon comparison of the published COI-3P sequences with our COI reference dataset (data not shown) we conclude this lineage to match a cluster that includes B. nigrotibialis, B. nigrifacia and B. nigrofemoralis, which share some of the same hosts as B. correcta and can be morphologically similar (Allwood et al 1999;Drew and Romig 2013). For maximum likelihood tree inference of the relationships of the target species and their closest relatives (based on (San Jose et al 2018a), we used unique haplotypes only and added B. nigrotibialis (Perkins), Zeugodacus tau (Walker), Z. synnephes (Hendel) and Z. choristus (May) to the alignments.…”
Section: Phylogenetic and Population Genetic Analysessupporting
confidence: 89%
See 3 more Smart Citations
“…Also, Kunprom et al (Kunprom et al 2015) reported a strongly divergent COI lineage within B. correcta, matching earlier results based on the COI-3P region (Jamnongluk et al 2003). They attributed this anomaly to Wolbachia bacterial infection, but upon comparison of the published COI-3P sequences with our COI reference dataset (data not shown) we conclude this lineage to match a cluster that includes B. nigrotibialis, B. nigrifacia and B. nigrofemoralis, which share some of the same hosts as B. correcta and can be morphologically similar (Allwood et al 1999;Drew and Romig 2013). For maximum likelihood tree inference of the relationships of the target species and their closest relatives (based on (San Jose et al 2018a), we used unique haplotypes only and added B. nigrotibialis (Perkins), Zeugodacus tau (Walker), Z. synnephes (Hendel) and Z. choristus (May) to the alignments.…”
Section: Phylogenetic and Population Genetic Analysessupporting
confidence: 89%
“…The effects of historical climatic change were not as severe in Southeast Asia as in temperate regions, with more continuous possibilities for gene-flow throughout the region which may have resulted in less strongly pronounced biogeographic patterns (Penny 2001;Cannon and Manos 2003). However, a high resolution (1,097 SNPs) study of the melon fly Z. cucurbitae revealed geographic structuring with six to ten clusters that were only partly detected using microsatellite data (Dupuis et al 2018a), and are not detected in our current study using COI. Despite being a widespread species occurring from Africa across Asia into the Pacific, we only found a single dominant haplotype.…”
Section: Undetected(?) Biogeographic Patternscontrasting
confidence: 77%
See 2 more Smart Citations
“…The newer Fluidigm Juno system can also handle up to 192 samples in a single run, and multiplexing of primer pairs can allow for even higher throughput, provided that the primers do not interact during amplification. Double‐barcoded amplicons can also be generated by other means using approaches such as traditional or highly multiplexed PCR (e.g., Bybee et al., ; Dupuis et al., ).…”
Section: Dependencies For the Fluidigm2purc Pipelinementioning
confidence: 99%